Enhancing Student Entrepreneurship Through Business Incubators - Ramli, Rahmat (Malaqbi Publisher, 2025)
Business incubators in higher education institutions serve as a platform to nurture entrepreneurial talent among students. This study aims to evaluate the impact of the University X business incubator program in enhancing entrepreneurial abilities and supporting successful venture creation among Business Administration students. A mixed-methods approach was utilized, combining quantitative surveys of 150 participants with in-depth interviews of 15 alumni entrepreneurs. The study revealed significant improvements in entrepreneurial competencies, professional networking, and business outcomes. Notably, students who joined the incubator showed a 75% business success rate post-graduation, compared to 35% among non-participants. These findings underscore the strategic role of academic incubators in shaping future job creators and advancing socio-economic development.